MICRONUTRIENTS DEFICIENCY IN PROTEIN CALORIC MALNUTRITION (PCM) - Rahman, Syed Kaleem; Waheed, Asma; Zeb, Rifaq; Afridi, Mukhtar (Khyber Journal of Medical Sciences, 2022)
Objective: To know about micronutrients deficiency in Children with PCM compared to standard values. Methods: This cross sectional study was conducted at department of pediatric Khyber Teaching Hospital Peshawar from January 2017 to December 2017.Total of 100 patients who were diagnosed as PCM using Z scoring were included in the study. Data was calculated by non probability sampling technique using predesigned questionnaire including questions of interest. The data was analyzed with SPSS 18. For continuous variables like Hb level, ferritin level mean and SD was calculated while for categorical variables frequency and percentage was calculated. For comparison of Hb and Ferritin level with standard value one sample T test was used. Results: Out of total 100 study population 44 were male,56 females, 40 from urban while 60 from rural area. Age of the patients showed that children of age from 8 - 14 months have maximum number of micronutrient deficiency, after 20 months, it slightly decreased but by 30 months again the number of children increases. Though there is downfall at 35 months but raises again by 40 months of life. When different variables of our study population were compared with standard normal level we found a significant difference between Hb (Mean 8.118 ±2.4, p<0.001), ferritin (Mean 186.27 ±373, p 0.01),zinc(Mean 77.08 ±21.9, p<0.001 ), and calcium level(Mean 6.9 , p <0.001 ). Conclusion: We found a significant difference between Hemoglobin, ferritin, zinc and calcium level of our study population and standard values.